3D lightweight mechanical metamaterial with nearly isotropic inelastic large deformation response. (December 2022) - Chen, Xueyan; Moughames, Johnny; Ji, Qingxiang; Martínez, Julio Andrés Iglesias; Tan, Huifeng; Ulliac, Gwenn; Laude, Vincent; Kadic, Muamer
Abstract: Well-designed stretching-dominated lattices can form elastic metamaterials with high specific stiffness and strength. Their strongly anisotropic and unstable nonlinear mechanical properties, however, limit their application to energy absorption. In contrast, bending-dominated lattices are well known for high energy absorption capacity and stable nonlinear response, but poor elastic response. Here, we propose a new class of light-weight elastic isotropic bending-dominated truss lattice that combines both advantages. Numerical simulations reveal that the proposed lattices not only exhibit elastic isotropy, but also nearly isotropic inelastic large deformation response. In particular, for a relative density smaller than 1% the metamaterial almost attains the upper bound of Poisson's ratio for an isotropic material, i.e ν = 0 . 5 . Compared to BCC truss lattices, uniaxial compression tests show that the relative modulus is twice as large, and that the relative collapse strength and specific energy absorption are about 1.6 times as large. The designed metamaterial is thus a noteworthy alternative for load bearing, energy absorption, and transformation acoustics. Graphical abstract: Highlights: A class of isotropic metamaterial with stable inelastic large response is introduced. A model successfully predicts elastic modulus for the proposed lattice materials. Isotropy is nearly conserved in the inelastic large deformation response.